2009
DOI: 10.1590/s1678-77572009000500020
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of two root canal sealers and a commercial calcium hydroxide paste on THP1 cell line by Trypan Blue assay

Abstract: Objective:The aim of this investigation was to evaluate the cytotoxicity of two brands of root canal sealers, epoxy-resin based and zinc oxide-eugenol based, and one commercial calcium hydroxide paste on a monocyte cell line THP-1.Material and methods:Undiluted (crude extract) and diluted extracts to 10%, 1%, 0.1%, 0.01%, 0.001% and 0.0001% of the sealers were tested for cytotoxicity to THP-1 cells using the trypan blue assay. Extracts were obtained according to ISO standard. Data were analyzed statistically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…In the present ESR studies, it can be asserted that relative cytotoxicity of the materials can be evaluated by measurement of the radical concentration [32,33]. The literature has presented controversial opinion on the cytotoxicity of root canal materials [34][35][36]. Hence, further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the present ESR studies, it can be asserted that relative cytotoxicity of the materials can be evaluated by measurement of the radical concentration [32,33]. The literature has presented controversial opinion on the cytotoxicity of root canal materials [34][35][36]. Hence, further studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, 85% to 90% of cells were killed by crude extract of AH26 and ZOE-based sealers for 24 hours in monocyte cell line THP-1 (25), by 25 mg /mL dilution of methyacrylate-based sealer for 24 hours in HPDLCS (26), and by one half the extract of AH26 and endomethasone for 24 hours in L929 mouse fibroblasts (24). Because direct contact or crude extract of AH26 significantly reduced cell viability, we chose the dilutions of extraction media as previously described (10,24,25). Our results showed that CPC sealers (Sankin, CAPSEAL I, and CAP-SEAL II) showed cytotoxity.…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic reparative materials may come into direct contact with dental pulp cells, dental follicle cells, periodontal ligament cells, such as fibroblasts, osteoblasts, undifferentiated mesenchymal cells, among other cell types. Immortalized cell cultures are frequently used in cytotoxicity and bioactivity assays (8)(9)(10) and are recommended by international standards for testing new dental materials (11). Immortalized cell lines are more used due to their facility of culture and the higher phenotypical stability compared to primary cells, which become senescent after a limited number of cell passages (12).…”
Section: Introductionmentioning
confidence: 99%